The Relationship between Dietary Compliance of Hypertension Patients and Increased Blood Pressure in Hypertension Patients in the Internal Medicine Poly Room of Dr Rm Djoelham Binjai Hospital in 2019 - Nur Hasanah (Science Midwifery, 2019)
Diet is one way to treat hypertension without serious side effects because of its natural control methods. Reducing salt intake, increasing fiber, stopping bad habits such as smoking, drinking coffee, consuming alcohol, using vegetables and herbs and taking medication regularly will help in lowering blood pressure. The eating factor in dietary compliance is an important thing to consider in hypertensive patients. Patients with hypertension should adhere to a hypertension diet in order to prevent further complications. Patients with hypertension must continue to carry out a hypertension diet every day with the presence or absence of pain and symptoms. The purpose of the hypertension diet and hypertension treatment is to control the blood pressure of hypertensive patients to remain stable or normal blood pressure so that they can avoid hypertension and prevent complications, especially the heart and blood vessels that can cause death. The results of the study were 31 respondents, the majority of patients aged 45-59 years with a total of 18 people (58.1) and a minority at the age of 60-75 years with a total of 13 people (41.9).